2020
DOI: 10.4314/ajcem.v21i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with dengue fever among febrile patients attending secondary health facilities in Kano metropolis, Nigeria

Abstract: Background: The Nigeria Centre for Disease Control (NCDC) has categorized dengue fever as a priority epidemic-prone disease. Kano metropolis is a hub for international trade and has seen rapid population growth with unplanned urbanisation. This provides the right environment for dengue virus transmission and spread. Most fevers in Nigeria and Kano in particular are treated as malaria or typhoid. This study aimed to determine the prevalence and factors associated with dengue fever and dengue-malaria co-infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Cross-sectional studies in Kenya [22, 39] and Cameroon [30, 45] reported significantly low odds of acute dengue in the presence of malaria than in its absence (OR = 0.57, 95% CI, 0.40 – 0.82). Similar studies Nigeria [18, 20, 25, 32, 33, 35], Tanzania [17], Sierra Leone [23], DRC [34], Cameroon [31], Sudan [40, 42], and Senegal [21] ; however, showed no notable odds of acute dengue infection in the presence of malaria when compared to the absence of malaria (OR = 1.07, 95% CI, 0.58 –1.94). On the contrary, cross-sectional studies in Ethiopia [44], Nigeria [16, 29], Tanzania [36], and Cameroon [43] indicated higher odds of acute dengue infection in the presence of malaria than in its absence (OR = 6.98, 95% CI, 2.89 – 16.85).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…Cross-sectional studies in Kenya [22, 39] and Cameroon [30, 45] reported significantly low odds of acute dengue in the presence of malaria than in its absence (OR = 0.57, 95% CI, 0.40 – 0.82). Similar studies Nigeria [18, 20, 25, 32, 33, 35], Tanzania [17], Sierra Leone [23], DRC [34], Cameroon [31], Sudan [40, 42], and Senegal [21] ; however, showed no notable odds of acute dengue infection in the presence of malaria when compared to the absence of malaria (OR = 1.07, 95% CI, 0.58 –1.94). On the contrary, cross-sectional studies in Ethiopia [44], Nigeria [16, 29], Tanzania [36], and Cameroon [43] indicated higher odds of acute dengue infection in the presence of malaria than in its absence (OR = 6.98, 95% CI, 2.89 – 16.85).…”
Section: Resultssupporting
confidence: 75%
“…Cross-sectional studies in Kenya [22,39] and Cameroon [30,45] reported significantly low odds of acute dengue in the presence of malaria than in its absence (OR = 0.57, 95% CI, 0.40 -0.82). Similar studies Nigeria [18,20,25,32,33,35],…”
Section: The Interaction Of Plasmodium and Dengue Virusessupporting
confidence: 73%
See 2 more Smart Citations
“…Dengue virus antibodies (anti-DENV IgG) have been reported in the Guinea Savannah region of Nigeria with prevalence of 20.5% [20]. Likewise in Kano (north-western Nigeria) high prevalence of dengue IgM has been reported from patients reporting with febrile fever [21].…”
Section: Introductionmentioning
confidence: 99%